Low Molar Mass Dextran: One-Step Synthesis With Dextransucrase by Site-Directed Mutagenesis and its Potential of Iron-Loading - Wang, Tingting; Jiang, Zhiming; Wang, Yiya; Wu, Hao; Fang, Yan; Dong, Weiliang; Wu, Bin; Ma, Jiangfeng; Jiang, Min (Frontiers in Bioengineering and Biotechnology, 2021)
Iron dextran is a common anti-anemia drug, and it requires low molar mass dextran as substrate. In this work, we selected 11 amino acid residues in domain A/B of DSR-MΔ2 within a 5-angstrom distance from sucrose for site-directed mutagenesis by molecular docking. Mutation of Q634 did not affect the enzyme catalytic activity, but showed an obvious impact on the ratio of low molecular weight dextran (L-dextran, 3000-5000 Da) and relatively higher molecular weight dextran (H-dextran, around 10,000 Da). L-dextran was the main product synthesized by DSR-MΔ2 Q634A, and its average molecular weight was 3951 Da with a polydispersity index <1.3. The structural characterization of this homopolysaccharide revealed that it was a dextran, with 86.0% α(1→6) and 14.0% α(1→4) glycosidic linkages. Moreover, L-dextran was oxidized with NaOH and chelated with ferric trichloride, and an OL-dextran-iron complex was synthesized with a high iron-loading potential of 33.5% (w/w). Altogether, mutation of amino acids near the sucrose binding site of dextransucrase can affect the chain elongation process, making it possible to modulate dextran size.